SYSTEM OF "PHYTOPHAGOUS-HOST" RELATIONSHIPS ON THE EXAMPLE OF TOMATO AGROCENOSIS (Scientific journal of the Fergana State University, 2023)
In the article, the system of "phytophagous-host" relationships of insects is highlighted on the example of tomato agrocenosis. When insects belonging to several families are artificially fed with different organs of the plant in open conditions, it has been found that their food intake varies.In the course of research, it was explained that the calf's head (G. gryllotalpa), the worm (A.meticulosus) and the Colorado beetle (L.decemlineata) are perfectly specialized species for the tomato plant. Among the artificially fed insects, aphids (M.euphorbiae) showed a characteristic of rapid reproduction.Insects reared with a non-specialized plant organ are fed very little to avoid death. Their viability can last up to 2-3 days. Among the insects, tomato is a suitable plant for the species M. euphorbiae, Th. tabaci, L. decemlineata and H. armigera.The degree of influence of dominant and subdominant insects on tomato plants, which are the most important and serious pests, has been determined. In this, various changes in plants are defined as a criterion. It has been proven that the level of insect attack on tomato plants is high.